2014
DOI: 10.1016/j.apsusc.2014.09.198
|View full text |Cite
|
Sign up to set email alerts
|

Imaging, spectroscopic, mechanical and biocompatibility studies of electrospun Tecoflex® EG 80A nanofibers and composites thereof containing multiwalled carbon nanotubes

Abstract: The present study discusses the design, development and characterization of electrospun Tecoflex® EG 80A class of polyurethane nanofibers and the incorporation of multiwalled carbon nanotubes (MWCNTs) to these materials. Scanning electron microscopy results confirmed the presence of polymer nanofibers, which showed a decrease in fiber diameter at 0.5% wt. and 1% wt. MWCNTs loadings, while transmission electron microscopy showed evidence of the MWCNTs embedded within the polymer matrix. The fourier transform in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…It is well known that addition of CA can decrease the resistivity of polymeric systems, which in turn will promote a decreased conductivity and lower charge density of the jet during electrospinning . These effects can drastically affect in the elongation of the fiber while it is being formed, promoting an increase in fiber diameter, which is similar to reports where salts have been used as additives to reduce nanofiber diameter . In our case, the effect is attributed to the presence of CA in the polymeric solution, increasing the diameters of the nanofibers during electrospinning.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…It is well known that addition of CA can decrease the resistivity of polymeric systems, which in turn will promote a decreased conductivity and lower charge density of the jet during electrospinning . These effects can drastically affect in the elongation of the fiber while it is being formed, promoting an increase in fiber diameter, which is similar to reports where salts have been used as additives to reduce nanofiber diameter . In our case, the effect is attributed to the presence of CA in the polymeric solution, increasing the diameters of the nanofibers during electrospinning.…”
Section: Resultssupporting
confidence: 86%
“…The rationale to have increased fiber diameters could be explained due to the presence of CA in the electrospinning solution thereby increasing the viscosity of the solution and therefore, needs a high charge while electrospinning. In this connection, our research group has demonstrated a decrease in nanofiber diameter upon addition of MWCNTs and different salts to electrospun polyurethane, nylon 6, and poly(vinyl alcohol) . It is well known that addition of CA can decrease the resistivity of polymeric systems, which in turn will promote a decreased conductivity and lower charge density of the jet during electrospinning .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Carbon nanofibers (CNFs) exhibit intriguing mechanical strength, flexibility, thermal conductivity [15][16] and have been widely used in various advanced composite materials, including polymeric composites [17][18][19], plastics [20][21][22], tissue scaffold [23][24] and energy storage devices [25][26][27]. M. H. Al-Saleh reported that tensile modulus and tensile strength of vapor grown CNFs were 2.92 GPa and 240 GPa [28].…”
Section: Introductionmentioning
confidence: 99%
“…CNT can be appropriate nanoparticle for developing structural and functional polymer‐based nanocomposites for biomedical applications as well . In addition to inherent exceptional properties of CNT enabling properties improvement of polymer/CNT nanocomposites, it is also able to induce the morphology of polymer matrix by promotion of crystallinity and trans ‐crystallinity which can in turn contribute significantly on the final mechanical properties of polymer/CNT nanocomposites .…”
Section: Introductionmentioning
confidence: 99%